Analisis Pengaruh Faktor Eksternal dan Internal Perusahaan Terhadap Harga Saham Syariah pada Sektor Barang Konsumen Primer - Ai Diana; Dadang Hermawan; Rosma Pakpahan (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study aims to examine the impact of Inflation, World Oil Price, Company Size, and Return on Equity (ROE) on Sharia stock prices. Companies in the primary consumer goods sector registered with ISSI for the period 2013-2021 constitute the population of this study. Secondary data included stock price, inflation rate, world oil price, company size and ROE were obtained from the Indonesia Stock Exchange, Bank Indonesia, World Bank and companies financial statements. This study employed the panel data regression analysis method and hypothesis testing with Eviews 10. The results reveal that individually, company size and ROE have a positive and significant influence on stock prices, while inflation and world oil prices have a positive and insignificant influence on stock prices. Simultaneously, inflation, world oil prices, company size and profitability have a significant influence on stock prices. Keywords: Internal factors; External factors; Stock prices